Electron Tomography Reveals the Droplet Covered Surface Structure of Nanowires Grown by Aerotaxy. Issue 33 (12th July 2018) - Persson, Axel R.; Metaferia, Wondwosen; Sivakumar, Sudhakar; Samuelson, Lars; Magnusson, Martin H.; Wallenberg, Reine
Abstract: For the purpose of functionalizing III‐V semiconductor nanowires using n‐doping, Sn‐doped GaAs zincblende nanowires are produced, using the growth method of Aerotaxy. The growth conditions used are such that Ga droplets, formed on the nanowire surface, increase in number and concentrations when the Sn‐precursor concentration is increased. Droplet‐covered wires grown with varying Sn concentrations are analyzed by transmission electron microscopy and electron tomography, which together establish the positioning of the droplets to be preferentially on {−111}B facets. These facets have the same polarity as the main wire growth direction, [−1−1−1]B. This means that the generated Ga particles can form nucleation sites for possible nanowire branch growth. The concept of azimuthal mapping is introduced as a useful tool for nanowire surface visualization and evaluation. It is demonstrated here that electron tomography is useful in revealing both the surface and internal morphologies of the nanowires, opening up for applications in the analysis of more structurally complicated systems like radially asymmetrical nanowires. The analysis also gives a further understanding of the limits of the dopants which can be used for Aerotaxy nanowires. Abstract : Electron tomography analysis of GaAs Aerotaxy nanowires is applied to determine the distribution of surface droplets. The high‐resolution imaging, 3D images, and a technique called azimuthal maps clearly show that the droplets prefer to end up on {−111}B, which can be of interest for future secondary growth of branches in the Aerotaxy setup.